Issues and complexities in safety culture assessment in healthcare - Ellis, Louise A.; Falkland, Emma; Hibbert, Peter; Wiig, Siri; Ree, Eline; Schultz, Timothy J.; Pirone, Christy; Braithwaite, Jeffrey (Frontiers in Public Health, 2023)
The concept of safety culture in healthcare – a culture that enables staff and patients to be free from harm – is characterized by complexity, multifacetedness, and indefinability. Over the years, disparate and unclear definitions have resulted in a proliferation of measurement tools, with lack of consensus on how safety culture can be best measured and improved. A growing challenge is also achieving sufficient response rates, due to ‘survey fatigue’, with the need for survey optimisation never being more acute. In this paper, we discuss key challenges and complexities in safety culture assessment relating to definition, tools, dimensionality and response rates. The aim is to prompt critical reflection on these issues and point to possible solutions and areas for future research